The cowboy takes a bride [large type] - Clopton, Debra (Mule Hollow series, 2009)
Sugar Rae Lenox is famous in Mule Hollow for wanting her name in lights on a Hollywood marquee, for wanting to leave, and for thinking the local matchmakers are mighty mistaken! Why applaud the attraction between her and a too-handsome cowboy with boots of lead? Ross Denton lives on the outskirts of town on a dusty ranch, and the only place he wants to see his name is on a marriage certificate. So why isn't Sugar Rae singing and dancing away from that ranch? She can't possibly want a starring role as Ross's bride, can she?